In Vitro Culture of Dragon Fruit (Hylocereus polyrhizus): Callus and Anthocyanin Production - I. Indarwati (Agrotech Journal, 2021)
Tissue culture biotechnology has been widely used to produce secondary metabolites. Anthocyanin as the secundary metabolic content in Dragon Fruits was thought to be able to liberate free radicals and have pharmacological activities as antioxidants and anti-aging. Anthocyanin can be produced in vitrothrough callus production by tissue culture. The study aims to produce callus cultures that have the potensial to produce secondary metabolites. This research was conducted in the tissue culture laboratory. The study used a completely randomized design method with a factorial pattern. Factor 1 : Type of explants ( M1): Explants from young shoots; (M2) Explants from dragon fruit callus. Factor II: The number of explant each culture tube. There are J1,J2, 3 and J4 with (1;2;3;4 explants in each culture tube. Murashige and Skoog + 15 % sucrose were used as media culture. The results of study showed that: callus began to form at 7 weeks after planting. (1) MS Media with the addition of 15 % sucrose had a significant effect on increasing the anthocyanin content in the callus of Dragon fruit formed. (2) Callus formed from Shoot Dragon fruit contain Anthocyanin 0,74 % ; (3) The Callus formed from Shoot and callus Dragon Fruits contain secondary martabolites of Anthocyanins ranging from 0,68%–0,76%. The highest Anthocyanin content (0,76%) was produced in treatmant J3 ( 3 Explant each culture tube)